The Resistance of Women Victims of Domestic Violence in the Film Bolehkah Sekali Saja Kumenangis (Sara Mills' Critical Discourse Analysis) - Nadia Nasywa Annabila; Arif Ardy Wibowo (Jurnal Riset Komunikasi (JURKOM), 2026)
Domestic violence represents a form of gender inequality that continues to persist in patriarchal societies, placing women in vulnerable and oppressive positions within the domestic sphere. As a medium, film functions not only as entertainment but also as a site that reflects power relations and social representations shaping public perceptions of gender and violence. This study aims to analyze how the resistance of women who experience domestic violence is constructed in the film Bolehkah Sekali Saja Kumenangis. The research employs a descriptive qualitative method with Sara Mills’ Critical Discourse Analysis to examine the concepts of subject position, object position, and reader position in constructing the meaning of resistance. The findings indicate that the film portrays women not merely as objects of violence but as subjects who engage in both verbal and nonverbal forms of resistance, offering a critical reading of patriarchal power relations within the family.